What is the added value of incorporating pleasure in sexual health interventions? A systematic review and meta-analysis - Zaneva, M; Philpott, A; Singh, A; Larsson, G; Gonsalves, L (Public Library of Science, 2022)
Despite billions of dollars invested into Sexual and Reproductive Health and Rights (SRHR) efforts, the effect of incorporating sexual pleasure, a key driver of why people have sex, in sexual health interventions is currently unclear. We carried out a systematic review and meta-analysis following PRISMA guidelines across 7 databases for relevant articles published between 1 January 2005–1 June, 2020. We included 33 unique interventions in our systematic review. Eight interventions reporting condom use outcomes were meta-analyzed together with a method random effects model. Quality appraisal was carried out through the Cochrane Collaborations’ RoB2 tool. This study was pre-registered on Prospero (ID: CRD42020201822). We identified 33 unique interventions (18886 participants at baseline) that incorporate pleasure. All included interventions targeted HIV/STI risk reduction, none occurred in the context of pregnancy prevention or family planning. We find that the majority of interventions targeted populations that authors classified as high-risk. We were able to meta-analyze 8 studies (6634 participants at baseline) reporting condom use as an outcome and found an overall moderate, positive, and significant effect of Cohen’s d = 0·37 (95% CI 0·20–0·54, p < 0·001; I2 = 48%; τ2 = 0·043, p = 0·06). Incorporating sexual pleasure within SRHR interventions can improve sexual health outcomes. Our meta-analysis provides evidence about the positive impact of pleasure-incorporating interventions on condom use which has direct implications for reductions in HIV and STIs. Qualitatively, we find evidence that pleasure can have positive effects across different informational and knowledge-based attitudes as well. Future work is needed to further elucidate the impacts of pleasure within SRHR and across different outcomes and populations. Taking all the available evidence into account, we recommend that agencies responsible for sexual and reproductive health consider incorporating sexual pleasure considerations within their programming.